Efficacy of additional periprostatic apex nerve block on pain in each of 12 transrectal prostate core biopsies: a retrospective study - Jeong Woo Yoo; Kyo Chul Koo; Byung Ha Chung; Kwang Suk Lee (BMC Urology, 2021)
Abstract Background We identified pain variation according to prostate biopsy sites and compared differences in pain relief according to the site of periprostatic nerve block (PNB). Methods This retrospective study collected data from 312 patients who underwent transrectal prostate biopsies between January 2019 and August 2020. Patients were stratified into two groups according to the site of local anesthesia (base vs. base and apex PNB), with each block achieved with 2.5 cm3 of 2% lidocaine. Pain scores were assessed using the visual analog scale at the following time points: probe insertion, PNB at base, PNB at apex, each of the 12 core biopsy sites, and 15 min after biopsy. The results were analyzed using a linear mixed model. Results The average pain scores were significantly higher in the base-only PNB group than were those in the base and apex PNB group (3.88 vs 2.82, p < 0.001). In the base-only PNB group, the pain scores increased from base to apex (p < 0.001), and the pain at each site also gradually increased as the biopsy proceeded (p < 0.001). In contrast, in the base and apex PNB group, there was minor change in pain scores throughout the procedure. Conclusions The pain scores varied at each site during the prostate biopsy. The provision of a base and apex PNB provided greater pain relief than does base-only PNB during prostate biopsy.